IMPLEMENTASI PEMBELAJARAN BERBASIS ACTIVE DEEP LEARNER EXPERIENCE (ADLX) DENGAN PENDEKATAN TERPADU UNTUK MENUMBUHKAN KARAKTER RELIGIUS PESERTA DIDIK KELAS I SDIT MUTIARA INSAN SUKOHARJO - Khoirunnisa, Aulia; Dwi Anggraeni Siwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of Active Deep Learner Experience (ADLX)-based learning with an integrated approach to fostering religious character at SDIT Mutiara Insan Sukoharjo. This study used a qualitative descriptive method. The research subjects included first-grade teachers, first-grade students, and other supporting data sources. Data collection techniques included observation, interviews, and documentation. Data validity was tested through triangulation of sources, techniques, and theories. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing. The results indicate that ADLX-based learning with an integrated approach is implemented through three stages: planning, implementation, and evaluation. In the planning stage, teachers develop learning tools by integrating religious values ​​into the learning materials. In the implementation stage, learning activities consist of an introduction, core, and conclusion that link the material to verses from the Quran and Hadith, as well as connecting it to daily life and an orientation toward the afterlife. In the evaluation stage, teachers conduct a comprehensive assessment of cognitive, affective, and psychomotor aspects, with an emphasis on the development of religious character. The implementation of this learning demonstrates the development of religious character, such as prayer habits, discipline in worship, and behavior that reflects Islamic values in daily life. Keywords: Active Deep Learner Experience (ADLX), Integrated Approach, Religious Character